'Breaching Neutrality': English prize-taking and Swedish neutrality in the First Anglo-Dutch War, 1651–1654. Issue 2 (3rd April 2019) - Murdoch, Steve
Abstract : This article considers the impact of English seizure of neutral Swedish vessels during the First Anglo-Dutch War, 1651–4. These actions were undertaken at a time when no bilateral diplomatic treaty existed between the two nations and thus the legal basis for such prize-taking was hotly disputed on both sides. Through an examination of extant sources in both England and Sweden, the article scrutinises a number of case studies in a period where the concept of any meaningful international maritime law remained primitive. It concludes with a review of the diplomatic machinations which sought to recover ships, goods or compensation in the years following the conclusion of the war.